Fabrication and Characterisation of Semi-Solid DSSCs Using Reduced Graphene Oxide (rGO) from Coal as a Filler in Polymer Gel Electrolytes - W. O. Sukmawati; L. Ardan; I. Saleh; L. Agusu; I N. Sudiana; I. Usman (Faculty Mathematics and Natural Sciences, Halu Oleo University, 2025)
In an effort to enhance the conductivity of TMSPMA-based polymer gel electrolytes (PGE), this study incorporated reduced graphene oxide (rGO) as a filler within the PGE matrix. The rGO was synthesized from sub-bituminous coal utilizing a modified Hummer method, while the PGE was formulated through a sol-gel process involving TMSPMA with varying proportions of rGO relative to the PGE. X-ray diffraction (XRD) measurements confirmed the presence of rGO, revealing a peak at a 2θ angle of 24.830° and a calculated crystalline size of 30.44 nm. Fourier-transform infrared spectroscopy (FTIR) characterization indicated that the identified functional groups were consistent with the molecular structure of TMSPMA. Impedance measurements conducted using an LCR meter demonstrated that the incorporation of rGO up to 0.04 g significantly enhanced the conductivity, achieving a value of 0.013 S/cm. Furthermore, photovoltaic performance testing of dye-sensitized solar cells (DSSC) indicated that the highest efficiency of 1.03% was attained with the PGE containing 0.04 g of rGO.